Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Photonic crystal cavities with metallic Schottky contacts - Quiring, W.; Al-Hmoud, M.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Applied Physics Letters)
We report about the fabrication and analysis of high Q photonic crystal cavities with metallic Schottky-contacts. The structures are based on GaAs n-i membranes with an InGaAs quantum well in the i-region and nanostructured low ohmic metal top-gates. They are designed for photocurrent readout within the cavity and fast electric manipulations. The cavity structures are characterized by photoluminescence and photocurrent spectroscopy under resonant excitation. We find strong cavity resonances in the photocurrent spectra and surprisingly high Q-factors up to 6500. Temperature dependent photocurrent measurements in the region between 4.5K and 310K show an exponential enhancement of the photocurrent signal and an external quantum efficiency up to 0.26.